Visually Imperceptible Liquid‐Metal Circuits for Transparent, Stretchable Electronics with Direct Laser Writing. Issue 12 (6th February 2018) - Pan, Chengfeng; Kumar, Kitty; Li, Jianzhao; Markvicka, Eric J.; Herman, Peter R.; Majidi, Carmel
Abstract: A material architecture and laser‐based microfabrication technique is introduced to produce electrically conductive films (sheet resistance = 2.95 Ω sq −1 ; resistivity = 1.77 × 10 −6 Ω m) that are soft, elastic (strain limit >100%), and optically transparent. The films are composed of a grid‐like array of visually imperceptible liquid‐metal (LM) lines on a clear elastomer. Unlike previous efforts in transparent LM circuitry, the current approach enables fully imperceptible electronics that have not only high optical transmittance (>85% at 550 nm) but are also invisible under typical lighting conditions and reading distances. This unique combination of properties is enabled with a laser writing technique that results in LM grid patterns with a line width and pitch as small as 4.5 and 100 µm, respectively—yielding grid‐like wiring that has adequate conductivity for digital functionality but is also well below the threshold for visual perception. The electrical, mechanical, electromechanical, and optomechanical properties of the films are characterized and it is found that high conductivity and transparency are preserved at tensile strains of ≈100%. To demonstrate their effectiveness for emerging applications in transparent displays and sensing electronics, the material architecture is incorporated into a couple of illustrative use cases related to chemical hazard warning. Abstract : A visually imperceptible liquid‐metal–elastomer conductor for stretchable electronics is presented using the direct laser writing technique. This material architecture shows the unique combination of low sheet resistance ( R s < 3 Ω sq −1 ), high transmittance ( T > 85%), and large extensibility (ε > 100%), and is visually imperceptible. This enables new applications in "second skin" wearable computing, human–computer interaction, and soft robotics, which depend on soft, elastic, and optically transparent functionality.